2014
DOI: 10.5993/ajhb.38.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Rural Appalachian Perspectives on Heart Health: Social Ecological Contexts

Abstract: Comprehensive intervention guided by a social ecological framework is needed to address CVD risk reduction in Appalachian Kentucky communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…Compared to physical activity and dietary practices, even less is known about the social factors influencing tobacco use in rural settings. However, studies in rural Appalachian adults found encouragement from friends and family to be a primary motivator of smoking cessation, while frequent smoking in social circles hindered quitting efforts …”
mentioning
confidence: 99%
“…Compared to physical activity and dietary practices, even less is known about the social factors influencing tobacco use in rural settings. However, studies in rural Appalachian adults found encouragement from friends and family to be a primary motivator of smoking cessation, while frequent smoking in social circles hindered quitting efforts …”
mentioning
confidence: 99%
“…Despite being socioeconomically disadvantaged and encountering numerous barriers to living healthy lives [16][17][18][19][20] , rural residents are more likely to be obese than urban residents, independent of diet, physical activity, and sociodemographic factors 2,3,21,22 . These studies support a growing body of research suggesting that broader neighborhood characteristics are associated with poor health outcomes independent of individual-level factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing education attainment is reported to be more strongly associated with declining obesity prevalence in urban compared to rural areas 2,63 . This may be due to challenges faced by rural residents to access affordable, high-quality healthy foods and opportunities for physical activity 17,[64][65][66] . Higher education may therefore be overshadowed by financial constraints and limited opportunities to engage in healthy behaviors among rural residents.…”
mentioning
confidence: 99%
“…The Appalachia Regional Commission (ARC) reports that per capita personal income, real wages, salaries per job, and market income are significantly lower in all communities in Appalachian areas, compared with the respective state's averages . The Appalachian region has higher disease rates of stroke and cardiovascular disease . The Appalachian region has also been the subject of numerous other health‐related investigations including studies of healthcare access and utilization of services, diabetes, and relative rates of so‐called modifiable risk factors of disease and morbidity …”
mentioning
confidence: 99%
“…6 The Appalachian region has higher disease rates of stroke and cardiovascular disease. [7][8][9] The Appalachian region has also been the subject of numerous other health-related investigations including studies of healthcare access and utilization of services, diabetes, and relative rates of so-called modifiable risk factors of disease and morbidity. [10][11][12] There have been few studies comparing the prevalence of self reported hypertension between Appalachian residents and non-Appalachian residents.…”
mentioning
confidence: 99%